Integral Representations Of Functions That Are Holomorphic In Some Sochs - Madraximov Ruzimbay Masharipovich (Peerian Journals Publishing, 2022)
The concept of half-balls is introduced into the state. The polytope includes the Cauchy kernel, the invariant Poisson integral. The integral image of a holomorphic function is converted into a polyball.
Keywords: Unit ball; Unit polyball; invariant Poisson's integral; Cauchy kernel